Bacteriophage Based Assays for Detection of Salmonella Organisms - Vimlesh Gupta; Hari Mohan Saxena (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
Salmonellosis is an important zoonotic disease but fi eld applicable, simple, accurate, and cost effective diagnostics are lacking. We isolated a broad acting bacteriophage lytic to Salmonella Typhimurium, S. Pullorum, S. Gallinarum and S. Dublin and investigated its application in diagnosis employing MTT assay and nitrate test. On addition of MTT (3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) to live bacteria alone of isolates of Salmonella, its color changed from yellow to purple. However, after 4 hours of incubation of bacteria with bacteriophage, no color change was observed because of lysis of bacteria by the phage. After incubation with salmonellaphage, twelve out of forty clinical samples showed no colour change indicating lysis of Salmonella by phage, whereas samples without Salmonella showed colour change due to other bacteria. In nitrate test, live bacteria reduce nitrate to nitrite which can be detected  by change in colour. No colour developed on prior incubation of Salmonella with the phage.